PENGARUH TERAPI AUDITORY HYPNOSIS LIMA JARI TERHADAP TINGKAT KECEMASAN MAHASISWA MENGHADAPI TUGAS AKHIR DI MASA PANDEMI COVID 19 - Neneng Irma Oktaviani; Ayu Pratiwi; H.A.Y.G. Wibisomo (Nusantara Hasana Journal, 2022)
Students are one of the groups of people who are vulnerable to mental health problems. Several studies have shown high rates of psychological morbidity in college students worldwide, particularly related to depression and anxiety. Objective to determine the effect of 5 finger audiotory hypnosis therapy on the level of student anxiety in facing the final project during the covid-19 pandemic. This research use a research design that is experimental (quasi-experimental) without a control group. This study uses the One Group Pretest–Posttest design, in which there is no comparison (control) group, but at least the first observation (pretest) has been carried out which allows testing of changes after the intervention. Based on the results of the Wilcoxon Signed Rank Test calculation, the Z value obtained is -4.776 with a p value (Asymp.Sig 2 tailed) of .000 which is less than the critical research limit of 0.05 so that the hypothesis decision is to accept H1 or which means there is a significant difference between the pre-test and post-test groups. There is a significant difference in anxiety in final project students before being given five-finger hypnosis therapy and after being given five-finger hypnosis therapy.